A literature review of diagnosing transient synovitis hip disease: English - Panji - Sananta; Agung Ismanuworo; Eka Noviya Fuzianingsih (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Transient synovitis (TS), an abrupt, non-specific synovium inflammation, is the most prevalent cause of pediatric hip discomfort. Transient synovitis affects 3–10-year-olds. This disease is benign and self-limiting, but clinicians must distinguish it from an acute infection. After ruling out other causes of hip discomfort and limping, clinicians detect transient synovitis. Based on the patient's history, physical examination, and hip radiography, septic arthritis (SA) and TS care are the most likely causes. Clinicians must consider clinical factors and order appropriate lab and imaging tests to rule out alternative illnesses. This review aims to determine how to propose TS hip disease. The databases used were Scopus and PubMed. We included seven articles in our review. Clinical symptoms, lab testing, and radiographs determine the diagnosis. Ultrasound is a useful TS diagnostic tool since it is widely available, and children are not directly exposed to ionizing radiation. If TS and SA illnesses, which are commonly linked, are unclear, detecting bone marrow abnormalities, soft tissue lesions, synovial enhancement, and joint effusion by MRI can be beneficial. Laboratory tests help distinguish TS from SA because there are more extensive evaluations. Additionally, the healthcare provider performs a hip joint aspiration examination under ultrasound or fluoroscopy.